(untitled) (Teaching and Learning Inquiry, 2021)
What does someone embarking on a scholarship of teaching and learning (SoTL) project need to know about how students learn? And how can the SoTL novice reconcile their goals to improve teaching and learning with the vastness of the literature on the science of learning? In this article, we consider the complexity of this literature and its intersection with SoTL. We also review several popular books and websites that might be used by the SoTL novice as entry points for grounding their SoTL studies, informing the questions they ask and narrowing the literature they read. In these brief reviews, we offer practical tips and advice on how to use these resources effectively so that one does not have to become an expert in the science of learning to perform outstanding SoTL research.